(E)-N'-Arylidene-2-(4-oxoquinazolin-4(3H)-yl) acetohydrazides: Synthesis and evaluation of antitumor cytotoxicity and caspase activation activity. (1st January 2019) - Huan, Le Cong; Phuong, Cao Viet; Truc, Le Cong; Thanh, Vo Nguyen; Pham-The, Hai; Huong, Le-Thi-Thu; Thuan, Nguyen Thi; Park, Eun Jae; Ji, A Young; Kang, Jong Soon; Han, Sang-Bae; Tran, Phuong-Thao; et al.
Abstract: In our search for novel small molecules activating procaspase-3, we have designed and synthesised a series of novel acetohydrazides incorporating quinazolin-4(3 H )-ones (5, 6, 7) . Biological evaluation revealed eight compounds with significant cytotoxicity against three human cancer cell lines (SW620, colon cancer; PC-3, prostate cancer; NCI-H23, lung cancer). The most potent compound 5t displayed cytotoxicity up to 5-fold more potent than 5-FU. Analysis of structure-activity relationships showed that the introduction of different substituents at C-6 position on the quinazolin-4(3 H )-4-one moiety, such as 6-chloro or 6-methoxy potentially increased the cytotoxicity of the compounds. In term of caspase activation activity, several compounds were found to exhibit potent effects, (e.g. compounds 7 b, 5n, and 5l ). Especially, compound 7 b activated caspases activity by almost 200% in comparison to that of PAC-1. Further docking simulation also revealed that this compound potentially is a potent allosteric inhibitor of procaspase-3. Graphical Abstract: